Effects of cell-free DNA on kidney disease and intervention strategies - Zhang, Mingying; Cai, Yubin; Zhong, Xiaoze; Liu, Weijun; Lin, Yuan; Qiu, Zhanyi; Liang, Ruihuang; Wei, Huibo; Wu, Kefei; Liu, Qinghua (Frontiers in Pharmacology, 2024)
Kidney disease has become a global public health problem. Patients with end-stage kidney disease must rely on dialysis or undergo renal transplantation, placing heavy burdens on their families and society. Therefore, it is important to develop new therapeutic targets and intervention strategies during early stages of chronic kidney disease. The widespread application of liquid biopsy has led to an increasing number of studies concerning the roles of cell-free DNA (cfDNA) in kidney disease. In this review, we summarize relevant studies concerning the roles of cfDNA in kidney disease and describe various strategies for targeted removal of cfDNA, with the goal of establishing novel therapeutic approaches for kidney disease.